Entrepreneurial Interest and Business Formation Intention: Evidence from a PLS Structural Equation Model - Fatima Zahra Benyoussef; Yayuk Natrni (International Journal of Economics Business and Social Sciences, 2026)
Entrepreneurship has become an important driver of economic growth, innovation, and employment generation in many countries. One of the key factors influencing the emergence of new businesses is entrepreneurial interest, which reflects an individual’s motivation, attitude, and readiness to engage in entrepreneurial activities. Understanding how entrepreneurial interest shapes business formation intention is therefore essential for promoting sustainable entrepreneurial ecosystems. This study aims to examine the relationship between entrepreneurial interest and business formation intention using a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. A quantitative research design was employed by collecting data through structured questionnaires distributed to respondents with potential involvement in entrepreneurial activities. The study analyzes several dimensions of entrepreneurial interest, including motivation, risk-taking attitude, creativity, and opportunity recognition, and investigates their influence on individuals’ intentions to establish new businesses. The PLS-SEM method was used to evaluate both the measurement model and the structural relationships among variables. The results indicate that entrepreneurial interest has a significant and positive effect on business formation intention. Individuals with higher levels of entrepreneurial motivation, innovative thinking, and willingness to take calculated risks are more likely to demonstrate strong intentions to start a business. In addition, opportunity recognition and personal confidence in entrepreneurial capabilities further strengthen this relationship. These findings suggest that fostering entrepreneurial interest through education, training programs, and supportive institutional environments can significantly enhance the likelihood of new business creation.